IJEPA: Gray Area for Health Policy and International Nurse Migration. (May 2017) - Efendi, Ferry; Mackey, Timothy Ken; Huang, Mei-Chih; Chen, Ching-Min
Indonesia is recognized as a nurse exporting country, with policies that encourage nursing professionals to emigrate abroad. This includes the country's adoption of international principles attempting to protect Indonesian nurses that emigrate as well as the country's own participation in a bilateral trade and investment agreement, known as the Indonesia–Japan Economic Partnership Agreement that facilitates Indonesian nurse migration to Japan. Despite the potential trade and employment benefits from sending nurses abroad under the Indonesia–Japan Economic Partnership Agreement, Indonesia itself is suffering from a crisis in nursing capacity and ensuring adequate healthcare access for its own populations. This represents a distinct challenge for Indonesia in appropriately balancing domestic health workforce needs, employment, and training opportunities for Indonesian nurses, and the need to acknowledge the rights of nurses to freely migrate abroad. Hence, this article reviews the complex operational and ethical issues associated with Indonesian health worker migration under the Indonesia–Japan Economic Partnership Agreement. It also introduces a policy proposal to improve performance of the Indonesia–Japan Economic Partnership Agreement and better align it with international principles focused on equitable health worker migration.